Towards greater inter-regional collaboration : new directions in Guyana-Brazil relations. - Kirton, Mark (1991)
Assesses the scope and direction of the relations between Guyana and Brazil since 1968. Identifies the problems as well as the prospects for future interaction between Brazil and the small states of the Caribbean.